SAT0656 DAPSA OR MDA/VLDA CRITERIA FOR DEFINING THE TREATMENT TARGET IN PSORIATIC ARTHRITIS? CROSS-SECTIONAL ANALYSIS FROM A MULTICENTER ITALIAN COHORT. (June 2019) - Favalli, Ennio Giulio; Idolazzi, Luca; Bugatti, Serena; Batticciotto, Alberto; Quartuccio, Luca; Filippini, Matteo; Parisi, Simone; Biggioggero, Martina; Fassio, Angelo; Zanframundo, G; Guggino, Giuliana; Giovannini, I; et al.
Abstract : Background: According to international recommendations, psoriatic arthritis (PsA) should be managed by a treat-to-target approach, but the identification of the best tool for defining the target of remission/low disease activity (LDA) is still controversial. Objectives: To evaluate and compare the rates of remission/LDA by comparing Disease Activity in PSoriatic Arthritis (DAPSA) score with Very Low Disease Activity (VLDA)/Minimal Disease Activity (MDA) criteria in a real-life multicentre cohort of PsA patients. Methods: We performed a cross-sectional analysis including the first consecutive 500 PsA patients evaluated in 8 Italian rheumatology centres since September 2017. The rates of patients achieving DAPSA remission/LDA and VLDA/MDA were calculated and compared by a chi-square test. The agreement between the two criteria sets was established by Cohen's kappa. The proportion of patients with residual disease activity despite remission/LDA and VLDA/MDA was computed for: peripheral arthritis (number of swollen [SJ] or tender joints [TJ] ≥1), Leeds Enthesitis Index (≥1), number of dactylitis (≥1), Body Surface Area (BSA, ≥3%), Patient Global Assessment (PGA, ≥20), Health Assessment Questionnaire (HAQ, ≥0.5), pain VAS (≥15), C-reactive protein (CRP, ≥1 mg/dL). Sub-analyses after stratification according to ongoing treatment (csDMARDs versus bDMARDs) were also performed. Results: The study population (53.2% men; mean [± standard deviation, SD] age 52.9±12 years; mean [±SD] disease duration 8.6±7.7 years) included 200 patients treated with csDMARDs (71% methotrexate) and 300 with bDMARDs (73% anti-TNF agents). The rates of DAPSA remission and VLDA were similar in the overall population (25.8 vs 22.2%, respectively; p=0.18) and in bDMARD subgroup (27.3 vs 26.7%, respectively; p=0.85), but greater for DAPSA remission in csDMARD patients (23.5 vs 15.5%, respectively; p=0.04). DAPSA LDA was significantly more frequent than MDA (40.6 vs 26.4%, respectively; p<0.0001), with no significant difference in bDMARD vs csDMARD subgroups. The level of agreement was good between DAPSA remission and VLDA (kappa=0.72), but only fair between DAPSA LDA and MDA (kappa=0.30), with a higher agreement in bDMARD than csDMARD patients for both DAPSA remission/VLDA (kappa 0.74 vs 0.6, respectively) and DAPSA LDA/MDA (kappa 0.34 vs 0.23, respectively). Levels of residual disease activity (figure 1 ) were similar for DAPSA remission and VLDA, with the exception of skin domain (22.4 vs 12.6%, respectively; p=0.04). Compared with patients in MDA, those in DAPSA LDA showed more frequently residual joint involvement (SJ 47.3 vs 32.6%, respectively, p=0.007; TJ 66 vs 42.2%, respectively, p<0.0001), elevated PGA (63.5 vs 40.9%, respectively, p<0.0001), and elevated HAQ (50.7 vs 36.3%, respectively, p<0.009). Conclusion: In our real-life cross-sectional analysis, the agreement between DAPSA and VLDA/MDA criteria was good only for the definition of remission, whereas DAPSA was significantly less stringent than MDA (especially in csDMARDs treated patients) in defining LDA, with a great proportion of patients showing residual arthritis and disability. Disclosure of Interests: Ennio Giulio Favalli: None declared, Luca Idolazzi: None declared, Serena Bugatti Speakers bureau: Bristol-Myers Squibb, Celgene, Lilly, Novartis, Sanofi, Janssen, Alberto Batticciotto: None declared, Luca Quartuccio: None declared, Matteo Filippini: None declared, Simone Parisi Speakers bureau: Chiesi, Jansenn, Pfizer, Celgene, Abbvie, Lilly., Martina Biggioggero: None declared, Angelo Fassio: None declared, G Zanframundo: None declared, Giuliana Guggino Grant/research support from: Laborest, Pfizer, Consultant for: Novartis, Abbvie, Speakers bureau: Sandoz, I Giovannini: None declared, Maria Chiara Ditto: None declared, Francesco Ciccia Grant/research support from: CELGENE, PFIZER, Consultant for: UCB, NOVARTIS, CELGENE, PFIZER, LILLY, Paid instructor for: UCB, NOVARTIS, CELGENE, PFIZER, LILLY, JANSSEN, Speakers bureau: UCB, NOVARTIS, CELGENE, PFIZER, LILLY, JANSSEN, MSD, ROCHE, AMGEN